Clinical value of conventional magnetic resonance imaging combined with diffusion-weighted imaging in predicting pelvic lymph node metastasis of cervical cancer - Fan, Leilei; Ma, Liguo; Ling, Rennan; Guo, Xiaojing; Li, Haili; Yang, Degui; Lian, Zhesi (Frontiers in Oncology, 2023)
Background In cervical cancer (CC), the involvement of pelvis lymph nodes is a crucial factor for patients’ outcome. We aimed to investigate the value of conventional magnetic resonance imaging (MRI) combined with diffusion-weighted imaging (DWI) and the apparent diffusion coefficient (ADC) in predicting CC pelvic lymph node metastasis (PLNM). Methods This retrospective study included CC patients who received surgical treatments. Surgical pathology results served as the gold standard for investigating the diagnostic performance of conventional MRI combined with DWI. We analyzed the association between tumor ADC and PLNM, as well as other pathological factors. The areas under the receiver operating characteristic curves (AUCs) for ADC in assessing PLNM and pathological factors were evaluated, and optimal cut-off points were obtained. Results A total of 261 CC patients were analyzed. PLNM patients had significantly lower tumor ADC (0.829 ± 0.144×10-3mm2/s vs. 1.064 ± 0.345×10-3mm2/s, p<0.0001), than non-PLNM CC. The agreement between conventional MRI combined with DWI and pathological results on PLNM diagnosis was substantial (Kappa=0.7031, p<0.0001), with 76% sensitivity, 94.31% specificity, and 90.8% accuracy. The AUC of tumor ADC was 0.703, and the optimal cut-off was 0.95×10-3 mm2/s. In multivariate analysis model 1, tumor ADC<0.95×10-3mm2/s was significantly associated with PLNM (OR, 2.83; 95%CI, 1.08–7.43; p= 0.0346) after adjusting for age and pathological risk factors. In multivariate analysis model 2, tumor ADC<0.95×10-3mm2/s (OR, 4.00; 95%CI, 1.61–9.89; p=0.0027), age<35 years old (OR, 2.93; 95%CI, 1.04–8.30; p=0.0428), increased tumor diameter on MRI (OR, 2.17; 95%CI, 1.18–3.99; p=0.0128), vaginal vault involvement on MRI (OR, 2; 95%CI, 1.002–3.99; p=0.0494) were independent predictors for PLNM. Tumor ADC<0.95×10-3mm2/s was significantly associated with higher risk of tumor diameter ≥4cm (OR, 2.60; 95%CI, 1.43–4.73; p=0.0017), muscular layer infiltration >1/2 (OR, 5.46; 95%CI, 3.19–9.34; p<0.0001), vaginal vault involvement (OR, 2.25; 95%CI, 1.28–3.96; p=0.0051), and lymphovascular space involvement (OR, 3.81; 95%CI, 2.19–6.63; p<0.0001). Conclusion Conventional MRI combined with DWI had a good diagnostic performance in detecting PLNM. The tumor ADC value in PLNM patients was significantly lower than that in non-PLNM patients. Tumor ADC <0.95×10-3mm2/s, age <35 years old, increased tumor diameter on MRI, vaginal vault involvement on MRI were independent predictors for PLNM.